A survey of final year pharmacy undergraduates' mentorship experience. (30th November 2022) - Gurung, R; Conway, A
Abstract: Introduction: The General Pharmaceutical Council (GPhC) Standard 7.3 for the initial education and training of pharmacists 1 states student pharmacists and trainee pharmacists must have access to pharmacy professionals to provide professional support and guidance by acting as role models and mentors. Four mentoring programmes exist for Brighton University undergraduates, available virtually in addition to external mentoring programmes, such as Royal Pharmaceutical Society (RPS) mentoring programme. Chang et al 2 studied RPS mentoring participants and found previous positive experiences inspired participants to participate in their programme. This work investigates 2021/2022 final year Brighton University pharmacy undergraduate mentoring experience. Aim: To survey final year pharmacy undergraduates' mentorship experience. Methods: An online survey consisting of 5-point Likert-scale statements and closed-ended questions, was designed, piloted, and distributed using the JISC online survey platform to final year Brighton University pharmacy undergraduates. Data collected included awareness of mentorship programmes, whether undergraduates had previous mentorship experience, and attitudes towards mentoring using 12 Likert-scale statements each for respondents who were mentors, mentees, and those with no mentoring experience. The data were quantitively analysed using Microsoft Excel version 16.58 and the JISC online survey platform. The 5-point Likert Scale questions were analysed by calculating a weighted average. Ethics approval was received from the Brighton University School of Applied Sciences Research Ethics Committee. Results: 48 undergraduates completed the survey. 13 (27%) had previous experience mentoring. This sample was comprised of 8 undergraduates with mentor experience and 10 undergraduates with mentee experience. Four undergraduates had both mentor and mentee experience. In total, 63% (n=39) respondents were aware of the University's mentoring programmes, 32 (60%) were aware of external mentoring programmes available with 45% (n=24) citing the RPS mentoring programme. A total of 75% (n=6) mentors and 70% (n=7) mentees reported that mentoring aided their professional development. All (n=8) undergraduates who were mentors and 80% (n=8) mentees reported that this was a beneficial experience. Three quarters (n=6) of those who were a mentor and 60% (n=6) who were mentees reported that this improved their employability skills. The main challenge found by mentors and mentees was the amount of time needed to undertake these roles. 16 (46%) undergraduates with no mentoring experience agreed that participating in a mentoring programme would be too much time and effort, 28 (80%) would prefer if their mentor/mentee was from or following the same professional background as them and 20 (57%) agreed they would consider signing up for a mentorship programme if offered to them. Discussion/Conclusion: Limitations included a low response, but results obtained were sufficient to highlight issues. Although most undergraduates were found to be aware of benefits of a mentorship programme, these should be promoted further, with realism around time mentoring takes, and opportunities scoped to incorporate time for mentoring in undergraduates' timetables. Many undergraduates still lack mentoring experience and are not aware of mentoring programmes. Establishing mentoring arrangements within the final year with trainee pharmacists could be a mechanism to address the undergraduate's preference of mentoring arrangements with the same professional background. References: 1. GPhC. Standards for the initial education and training of pharmacists2021 [cited 2021 10/11/2021]:[16-32 pp.]. Available from: https://www.pharmacyregulation.org/sites/default/files/document/standards-for-the-initial-education-and-training-of-pharmacists-january-2021_0.pdf 2. Chang H, Desselle S, Canedo J, Mantzourani E. Reflections of mentors and mentees on a national mentoring programme for pharmacists in the United Kingdom: An examination into organisational culture and systems. Research in Social and Administrative Pharmacy. 2021.